(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
The annotation for the topic "language universals and their characteristic features" explores the fundamental properties and patterns that are common across languages worldwide. It delves into the investigation of linguistic principles and structures that transcend individual languages, shedding light on recurring patterns in phonology, morphology, syntax, and semantics. The annotation discusses the significance of understanding language universals and their role in the study of language typology, historical linguistics, and cognitive science. Furthermore, it touches upon the cross-cultural and interdisciplinary relevance of language universals, emphasizing their impact on diverse linguistic traditions and the broader understanding of human cognition and communication. The annotation provides a comprehensive framework for exploring the characteristics and implications of language universals, prompting further inquiry into the nature of language diversity and the commonalities that underpin human speech and thought.